Gender-age distribution of tuberculosis among suspected tuberculosis cases in western Kenya - Henry DN Nyamogoba; Grace Mbuthia (Medicine Science, 2018)
Globally, tuberculosis (TB) continues to exact an unacceptably high toll of disease and death among children, particularly in the wake of the HIV epidemic. Kenya is ranked 13th among the 22 high-burden TB countries, and 5th in Africa. To determine the gender-age distribution of tuberculosis among TB suspects in western Kenya. In a cross-sectional study carried out at 10 hospitals in western Kenya, sputa from 872 TB suspects underwent microscopy and culture on solid and liquid media. The growth was identified using the Hains GenoType® Mycobacterium CM and GenoType® Mycobacterium AS kits. A questionnaire was used to collect demographic data. In total, 41.4% of the TB suspects were diagnosed with mycobacterial disease (95.8% TB cases and 4.2% NTM disease cases). Hence, 39.7% of the suspects were diagnosed with TB, 61.6% males and 38.4% females. A total of 263 (76%) of the 346 TB cases accepted to be tested for HIV infection and 41.8% (110/263) were co-infected (males, 55.5%; females, 44.5%). There was no significant difference in the TB-HIV co-infection rate between genders [OR = 1.006; 95% CI: 0.671-1.508; P = 0.979]. The majority (40.9%) of the TB/HIV cases were in the 25-34-year age bracket. In general, the prevalence of TB was significantly higher in males than females (χ2 = 10.67; P = 0.001), the majority (37.0%) being in the 25-34 age-group. Children below 15 years constituted 4.9% of the cases. A high prevalence of TB was observed in this study, males in the 25-34 age-group carrying the highest burden. There is need for more efforts and resources to increase knowledge and access TB and NTM syndromes care. [Med-Science 2018; 7(2.000): 252-6]